Effect of first trimester body mass index and gestational weight gain on maternal and neonatal outcomes: a cross-sectional study - Sah, Ram Bisheshwar; Sah, Mukesh Kumar; Sangroula, Raj Kumar; Yadav, Kamalesh Prasad; Rijal, Pappu; Thakur, Achala; Agrawal, Ajay (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Malnutrition and poor weight gain as well as maternal obesity have significant influences on the pregnancy outcome. This study aims to show the effect of first-trimester body mass index and the corresponding gestational weight gain on the outcome of pregnancy. Method: It was a cross-sectional study conducted from 2017 to 2018. The sample size of the study was 740 respondents, which is calculated based on N=Z²pq/d² formulae, where Z=1.96 for 95% CI, p=11.5, q=100-p and d=2.3(20%) of permissible error of prevalence. Frequency, percentage, mean and standard deviation were calculated for descriptive analysis. Chi-square test was used to find out the association for categorical variables. Odds Ratio and Logistic regression were also calculated for categorical variables. Result: Most of the women (57.3%) had normal Body Mass Index (BMI). Compared to women of adequate Gestational Weight Gain (GWG), the Odds Ratio of Hypertensive Disorder in Pregnancy (HDP), Gestational Diabetes Mellitus (GDM), induction of labor and instrumental/caesarean delivery for women of excessive GWG was 3.88(95%, CI 1.65-9.12, p<0.05), 0.63(95% CI 0.24-1.63), 1.87(95% CI 1.11- 3.15, p<0.05), and 1.93(95% CI 1.14-3.27, p<0.05) respectively. Compared to women of normal BMI, the Odds Ratio of HDP, GDM, induction of labor and instrumental /caesarean delivery for overweight/obese women were 2.32(95% CI 1.15-4.66, p<0.05), 1.94(95% CI 1.10-3.41, p<0.05), 1.15(95% CI 0.75-1.77), 1.48(95% CI 0.96-2.28), respectively. Regarding neonatal outcomes, the OR of macrosomia and APGAR score <7 at 1&5 minute in the overweight/obese-group were 1.61(95% CI 0.56-4.61), 1.24(95% CI 0.21-7.25), and 2.04(95% CI 0.07-55.3), respectively. Conclusion: Both overweight/obesity and excessive GWG are the risk factors of Hypertensive Disorder in Pregnancy, induction of labor, instrumental/cesarean delivery, macrosomia, and APGAR<7 at1&5 minutes.